Sperm DNA Integrity is Unaffected by Thiopurine Treatment in Men With Inflammatory Bowel Disease. (16th June 2018) - Grosen, Anne; Nersting, Jacob; Bungum, Mona; Christensen, Lisbet Ambrosius; Schmiegelow, Kjeld; Spanò, Marcello; Julsgaard, Mette; Cordelli, Eugenia; Leter, Giorgio; Larsen, Peter Braad; Hvas, Christian Lodberg; Kelsen, Jens
Abstract: Background and Aims: Sperm DNA integrity, concentration, and motility are suspected to be altered by thiopurines (azathioprine [AZA] and 6-mercaptopurine [6-MP]). We investigated the impact of thiopurines on semen quality in men with inflammatory bowel disease [IBD], by a comprehensive panel of semen analyses. Methods: Semen from 40 men with IBD, in remission on AZA/6-MP therapy, was prospectively collected and compared with samples from 40 healthy volunteers. Paired samples [off and on AZA/6-MP] were obtained from a subset of IBD patients, and blood and semen were collected to determine 6-MP transmission to the ejaculate. Sperm DNA fragmentation was evaluated via sperm chromatin structure assay [SCSA] and Comet analysis. Conventional World Health Organization [WHO] parameters, i.e. semen volume and sperm concentration, motility, and morphology, were assessed. Additionally, we measured thioguanine nucleotide [TGN] incorporation in sperm cell DNA. Results: Sperm DNA fragmentation levels did not differ between men with IBD on AZA/6-MP and healthy volunteers when evaluated by SCSA [ p = 0.23] and Comet analysis [ p = 0.72]. IBD patients on AZA/6-MP had significantly lower total and progressive sperm motility than healthy volunteers [48.5% versus 64.5%, p = 0.0003; 27.4% versus 43.3%, p = 0.0004; respectively], with no differences in concentration, volume, or morphology. The same trend was observed in the 10 paired samples. TGN incorporation was not detectable in sperm DNA, but 6-MP was detected in seminal plasma and correlated to blood levels [rs = 0.79, p = 0.02]. Conclusions: Thiopurines do not increase sperm DNA fragmentation but may impair sperm motility in this IBD cohort. Our findings support existing epidemiological data that thiopurine therapy is safe during preconception and should not be abandoned.